Developing a Smart Bracelet to Measure Blood Oxygen (SpO2) and Heart Rate Using MAX30102 Sensor and Arduino Board (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
With the increasing interest in wearable healthcare technologies, the development of smart devices to monitor vital signs has become essential to enhance the quality of medical care and improve patients' response to critical health conditions. This research aims to design and develop a smart bracelet capable of measuring blood oxygen (SpO2) and heart rate based on the MAX30102 sensor, which is characterized by high accuracy in measuring these values through optical absorption technology. The system includes an Arduino or ESP32 processing unit, along with a wireless communication unit (Bluetooth/Wi-Fi) to transfer data to a smartphone application or an OLED display screen. The device was tested on a group of users, where the results showed high accuracy compared to traditional medical devices. This research reflects the importance of integrating smart technology into personalized medicine, while providing proposed improvements to increase the efficiency and accuracy of the system.In addition, the system relies on signal processing algorithms to accurately extract vital values and reduce noise resulting from movement. The bracelet is also designed to be comfortable for daily use, with a low-consumption battery that ensures continuous operation for long periods. The evaluations included comparison of measurements with reference medical devices, which showed a low error rate within clinically acceptable limits. This research contributes to the development of wearable medical technologies, allowing individuals to proactively monitor their health and reduce the need for routine check-ups in medical facilities.